If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 5) = 7(2x + -6) Reorder the terms: (5 + X) = 7(2x + -6) Remove parenthesis around (5 + X) 5 + X = 7(2x + -6) Reorder the terms: 5 + X = 7(-6 + 2x) 5 + X = (-6 * 7 + 2x * 7) 5 + X = (-42 + 14x) Solving 5 + X = -42 + 14x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + X = -42 + -5 + 14x Combine like terms: 5 + -5 = 0 0 + X = -42 + -5 + 14x X = -42 + -5 + 14x Combine like terms: -42 + -5 = -47 X = -47 + 14x Simplifying X = -47 + 14x
| 6(3s+6)=54 | | 11m+1=8m+4 | | 6y-2=4y+14 | | 3(x+5)+5+1=31 | | -2(4x-9)=10 | | 12x-4+x=180 | | 9d^2+3d-5=0 | | 8(3m-2)=104 | | 41=6v-7 | | 42y-42y^2=20 | | (2x-1)(x+2)+(3x+1)(x-1)= | | 3(n+4)-8=11-(6-2n)52 | | 3*(2x-1)=9 | | 8x-2y=60 | | 7/(10x)=103/20 | | 4x=8x+32 | | x-0.7=5.5 | | 7x3/6 | | x*2x=50000 | | 3(2b-1)=27 | | 1/8x-1/8y=19 | | log(12)2+log(12)x=log(12)(x+7) | | 2x^3+12=0 | | -7-13=15 | | -4x+2y=34 | | 2x+7=-3x+8 | | (4x+7)=(7x-8) | | (6a^4b^3)(3ab^2)= | | X-4+12=12-2 | | 6xy*xy*4y= | | 2(4y-2)= | | (x+3)+(x-3)=1 |